2015
DOI: 10.3390/met5020743
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Properties of Aluminum and Magnesium Based Composites Containing Amorphous Reinforcement: A Review

Abstract: This review deals with the processing and properties of novel lightweight metal matrix composites. Conventionally, hard and strong ceramic particles are used as reinforcement to fabricate metal matrix composites (MMCs). However, the poor mechanical properties associated with the interfacial de-cohesion and undesirable reactions at (ceramic) particle-(metallic) matrix interface represent major drawbacks. To overcome this limitation, metallic amorphous alloys (bulk metallic glass) have been recently identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Varied metallic glassy particles have been successfully used as reinforcement in metal matrix composites; these include Mg- [11,12], Al- [13], Fe-[14e17], Zr-[18e21], Cu- [22,23] and Ni-based [24e26] metallic glassy particles. Recently, Gupta M et al [10,27] have summarized the ongoing advances in the field.…”
Section: Introductionmentioning
confidence: 98%
“…Varied metallic glassy particles have been successfully used as reinforcement in metal matrix composites; these include Mg- [11,12], Al- [13], Fe-[14e17], Zr-[18e21], Cu- [22,23] and Ni-based [24e26] metallic glassy particles. Recently, Gupta M et al [10,27] have summarized the ongoing advances in the field.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the above-mentioned advantages, it has been shown that metallic glass shows excellent strengthening effects in metals such as aluminum [12,21,24,25], magnesium [26] and copper alloys [27,28]. However, despite the high strengthening effect obtained for aluminum and aluminum alloys by adding MG reinforcement, the ductility of these AMMCs is still relatively low [29]. The main reason for this is that the MG reinforcements used are microparticles, where high local stress concentration can occur and cause microcracks [30].…”
Section: Introductionmentioning
confidence: 88%
“…However, owing to the difficulty of obtaining MG nanoparticles, preliminary works have mostly focused on micro-sized particle (>5 µm) reinforcing composites, and research on nano-sized metallic glass reinforcements has only rarely been performed [12,15]. Another challenge is that it is difficult to fabricate the composites with a uniform dispersion of MG nanoparticles [12,22,29]. In this work, a powder metallurgical route was developed to fabricate nanocomposite powder where MG nanoparticles are uniformly distributed in the Al alloy matrix, which may be beneficial for designing and fabricating the novel nanocomposites reinforced with metallic glass nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…(3) As a high laser power was employed, a high peak temperature was acquired correspondingly, and the resultant Marangoni convection was generated with a high velocity, favoring the Based on the above experiment results, it has been concluded that laser energy input can significantly influence the distribution of ex-situ Al 2 O 3 and in situ Al 2 Si 4 O 10 particles within the molten pool. The underlying factor contributing to the dispersion state of reinforcement is the input energy and resultant operative temperature [23][24][25]. For a clearer understanding of the distribution evolution of reinforcement particles, the corresponding schematics are shown in Figure 5b.…”
Section: Discussionmentioning
confidence: 99%